THE DREAM OF WHOLENESS: THE POETICS OF THE UNPREDICTABLE - Mojsilovic, Mila (Arhitektura i urbanizam, 2021)
By redefining the notion of fragmentarity and existing theoretical conceptions, from romantic fascination with ruins to the contemporary position of variability, the paper places incompleteness as the essential potentiality of form, imagination and contingency in a way that opens new space-time categories. In the paper, fragmentation is understood as a model for interpreting reality and for examining the capacity of architectural incompleteness. Setting complexity as the context, change as the method and variability as the model for understanding the architectural contemporaries within its reality, spatial and temporal uncertainty become characteristics of the fragmentation and destabilization of relations - their reflection. This way of structuring order out of chaos, or destabilizing order for the purpose of new structures, is the complexity of a higher order. The uncaptured nature of all things, in distracting the new, transports its own limitations, thematized through places of change, separation and path - specific singularities, allowing flexibility through imperfection. The elusive nature of all things, in opening to the new, transcends its own limitations, thematizing itself through places of change, separation and cracking. These are specific singularities that allow flexibility through incompleteness, thus opening up towards new forms of reality, between uncertainty and indeterminacy - in the zone of their overlap, space and time become fragmented. This true spontaneity is the greatest complexity that carries within itself the power of change and essential potentiality - a meaning that is always just emerging. The question of the degree of incompleteness is in the core of the concept of openness, in which the alteration of form and geometry take place.
Keywords: fragmentation; fragment; incompleteness; metastability